A study to determine factors contributing to the high rate of puerperal sepsis among women deliver at Lusaka urban clinics - Lyamba, J Sitwala (Lusaka: University of Zambia , School of Medicine, 1996)
The objective of the study was to determine the factors contributing to the high rate of puerperal sepsis among women who deliver at Lusaka urban clinics. Five clinics were randomly selcted for the purpose of this study.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Puerperal septicemia; Uterine hemorrhage